PENGARUH PEMBERIAN SOAL BERBASIS HIGHER ORDER THINKING SKILLS (HOTS) TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATA PELAJARAN AKIDAH AKHLAK DI MAN 2 PALEMBANG - Ismi Islamiaty; Karoma Karoma; Mardeli Mardeli; Sukirman Sukirman; Syarnubi Syarnubi (PAI RAFAH, 2020)
In the 21st century, with the rapid development of technology and science, the world seems to be challenged to improve quality in various aspects of life, one of which is education. Education is directed at preparing students who have thinking abilities and skills, especially higher-order thinking skills (HOTS), namely critical thinking. This study aims to determine the provision of Higher Order Thinking Skills (HOTS) based questions as a form of learning evaluation in order to determine the extent of students' critical thinking abilities. This research uses quantitative research, with samples taken by random sampling. The data obtained in this study were obtained from the results of a questionnaire (questionnaire) and documentation. Further analyzed with the collected data then recapitulated after the data was collected from various sources, then the data were analyzed using quantitative data analysis techniques. After analyzing the effect of giving Higher Order Thinking Skills (HOTS) based questions on the critical thinking skills of students at MAN 2 Palembang using the product moment correlation formula, it can be stated that there is a significant effect between the two variables, namely giving questions based on Higher Order Thinking Skills (HOTS) and ability. critical thinking. This is indicated by ttable = 2.02 and tcount = 3.17, then tcount> ttable. Then the coefficient of determination / destermination is 33%. This shows the effect of giving Higher Order Thinking Skills (HOTS) based questions on students' critical thinking skills at MAN 2 Palembang. While the remaining 67% of students' critical thinking skills at MAN 2 Palembang are influenced by other factors.